Novel Neonatal Variants of the Carbamoyl Phosphate Synthetase 1 Deficiency: Two Case Reports and Review of Literature - Yan, Beibei; Wang, Chao; Zhang, Kaihui; Zhang, Haiyan; Gao, Min; Lv, Yuqiang; Li, Xiaoying; Liu, Yi; Gai, Zhongtao (Frontiers in Genetics, 2019)
Carbamoyl phosphate synthetase I (CPS1) deficiency (CPS1D), is a rare autosomal recessive disorder, characterized by life-threatening hyperammonemia. In this study, we presented the detailed clinical features and genetic analysis of two patients with neonatal-onset CPS1D carrying two compound heterozygous variants of c.1631C > T (p.T544M)/c.1981G > T (p.G661C), and c.2896G > T (p.E966X)/c622-3C > G in CPS1 gene, individually. Out of them, three variants are novel, unreported including a missense (c.1981G > T, p.G661C), a nonsense (c.2896G > T, p.E966X), and a splicing change of c.622-3C > G. We reviewed all available publications regarding CPS1 mutations, and in total 264 different variants have been reported, with majority of 157 (59.5%) missense, followed by 35 (13.2%) small deletions. This study expanded the mutational spectrum of CPS1. Moreover, our cases and review further support the idea that most (≥90%) of the mutations were “private” and only ∼10% recurred in unrelated families.